A Detector for Premature Atrial and Ventricular Complexes - García-Isla, Guadalupe; Mainardi, Luca; Corino, Valentina D. A. (Frontiers in Physiology, 2021)
The relationship between premature atrial complexes (PACs) and atrial fibrillation (AF), stroke and myocardium degradation is unclear. Current PAC detectors are beat classifiers that attain low sensitivity on PAC detection. The lack of a proper PAC detector hinders the study of the implications of this event and its monitoring. In this work a PAC and ventricular detector is presented. Two PhysioNet open-source databases were used: the long-term ST database (LTSTDB) and the supraventricular arrhythmia database (SVDB). A combination of heart rate variability (HRV) and morphological features were used to classify beats. Morphological features were extracted from the ECG as well as on the 4th scale of the discrete wavelet transform (DWT). After feature selection, a random forest algorithm was trained for a binary classification of PAC (S) vs others and for a multi-labels classification to discriminate among normal (N), S and ventricular (V) beats. The algorithm was tested in a ten-fold cross-validation following a patient-wise train-test division (i.e. no beats belonging to the same patient were included both in the test and train set). The resultant median sensitivity, specificity and positive predictive value (PPV) were 99.29%, 99.54% and 100% for (N), 95.83%, 99.39% and 35.68% for (S), 100%, 99.90% and 79.63% for (V). The proposed method attains a greater PAC and ventricular beat sensitivity and PPV than the state-of-the-art classifiers.